PELATIHAN MODEL JIHAD KONTEKSTUAL: TAFSIR QS. AL-BAQARAH/2: 190 DI DI SEKOLAH ALDEPOS BOGOR - Hasan, Abdul Rokhim; Sakina, Siti; Kerwanto, Kerwanto; Sarnoto, Ahmad Zain; Ansori, Ansori; Choirunnisa, Choirunnisa (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This research is discussing about the contextual purpose of jihad, that is included in QS. Al-Baqarah/2:190 using the Abdullah Saeed’s contextual perspective. The method that is used in this research is maudhû’î research method and contextual Qur’an interpretation approach initiated by Abdullah Saeed. The result that we find out from this research is the purpose of jihad by war that is written in QS. Al-Baqarah/2: 190 is included into “instructional values” from the hierarchy of moral values in accordance with Abdullah Saeed’s application on contextual approach. Jihad by war is a form of jihad that could be adapted based on the situation and condition that is faced by the people, in social, political, and cultural aspects. Jihad by war is also a defensive action that is done to protect the people from enemy’s oppression and is a last option that could be done by Moslem people